Parents' Obligations in Educating Children's Morals - Sarianto, Debi; Pasaleron, Roni; Helena, Helena; Sumitra, Ade; Wahyuni Az-zahra, Dwi (Khalaqa: Journal of Education and Learning, 2024)
Based on the results of the initial observations made by the author, there is a lack of parental attention in providing moral education to children. This research aims to find out how parents educate their children about Aqidah, Worship and Morals. This study uses a descriptive qualitative research method, which describes the existing reality of Children's Moral Education. The results of the study show that parents in RT 01 RW 12 about children's Tawhid education have been done well, such as giving examples of example, teaching monotheism and teaching children about the five-time prayer procedure. Parents in educating their children in worship by inviting their children to pray in congregation at the mosque and enrolling their children in the existing TPQ. The way parents educate their children's morals by exemplifying good behavior with a patient attitude, not being arrogant, as well as keeping their mouths and not saying dirty things.